2022
DOI: 10.3390/cancers14020413
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Mutant GNAQ into Endothelial Cells Induces a Vascular Malformation Phenotype with Therapeutic Response to Imatinib

Abstract: GNAQ is mutated in vascular and melanocytic lesions, including vascular malformations and nevi. No in vivo model of GNAQ activation in endothelial cells has previously been described. We introduce mutant GNAQ into a murine endothelial cell line, MS1. The resultant transduced cells exhibit a novel phenotype in vivo, with extensive vasoformative endothelial cells forming aberrant lumens similar to those seen in vascular malformations. ATAC-seq analysis reveals activation of c-Kit in the novel vascular malformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A second xenograft model by Sasaki and colleagues, based on murine ECs expressing GNAQ p.Q209L, confirmed that the GNAQ -mutant ECs could form enlarged, ectatic vessels upon subcutaneous injection into mice ( 63 ).…”
Section: Models Of Cm/sws and Other Gnaq -Related ...mentioning
confidence: 88%
“…A second xenograft model by Sasaki and colleagues, based on murine ECs expressing GNAQ p.Q209L, confirmed that the GNAQ -mutant ECs could form enlarged, ectatic vessels upon subcutaneous injection into mice ( 63 ).…”
Section: Models Of Cm/sws and Other Gnaq -Related ...mentioning
confidence: 88%
“…Multiple candidates known to affect vascular function are inhibited either selectively or more potently by nilotinib compared to imatinib. Cell-free kinase inhibition studies and proteomic analyses have identified differential inhibition by nilotinib of multiple targets including TEK, SRC, KDR, FLT4, MAPK14, JAK1, DDR1, KIT, and PDGFRB 7 9 , 27 . Which target(s) are central to the mechanism of NAD remains to be assessed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrates that nilotinib has multiple distinct phenotypic effects on ECs, and these distinct effects could either represent independent off-target mechanisms or result from inhibition of a common pathway. Of note, while off-target inhibition likely contributes to NAD pathogenesis, the effect of nilotinib on off-target pathways may be therapeutic in other diseases such as Sturge-Weber Syndrome 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity of malignant cells and various stromal cellular components determine the diverse expression of different growth factors and cytokines. Platelet-derived growth factors (PDGFs) are commonly expressed in tumors and target stromal fibroblasts and perivascular cells through binding to platelet-derived growth factor receptors (PDGFRs) including PDGFRα or PDGFRβ [23,[27][28][29]. While angiogenic endothelial cell-derived PDGFs promote the recruitment of pericytes onto newly formed vessels [30][31][32], high levels of tumor cell-derived PDGFs can ablate pericytes from tumor vasculatures [33][34][35].…”
Section: Introductionmentioning
confidence: 99%